2019
DOI: 10.1016/j.ebiom.2019.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles and potential antagonistic mechanism between TGF-β and BMP pathways: Implications for cancer progression

Abstract: The transforming growth factor β (TGF-β) superfamily participates in tumour proliferation, apoptosis, differentiation, migration, invasion, immune evasion and extracellular matrix remodelling. Genetic deficiency in distinct components of TGF-β and BMP-induced signalling pathways or their excessive activation has been reported to regulate the development and progression of some cancers. As more in-depth studies about this superfamily have been conducted, more evidence suggests that the TGF-β and BMP pathways pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 139 publications
(146 reference statements)
3
60
0
Order By: Relevance
“…BMP activity in both regions was reduced (relative to myosin expression) ~50% in gnptab –/– morphants ( Figure 3F and Supplemental Figure 2 ). Due to significant crosstalk between the TGF-β and BMP signaling systems, high TGF-β activity has been shown to negatively impact BMP activity ( 46 , 47 ). To address this possibility, gnptab –/– morphants were treated at 52 hpf with the TGFBRI inhibitor SB505124 (10 μM).…”
Section: Resultsmentioning
confidence: 99%
“…BMP activity in both regions was reduced (relative to myosin expression) ~50% in gnptab –/– morphants ( Figure 3F and Supplemental Figure 2 ). Due to significant crosstalk between the TGF-β and BMP signaling systems, high TGF-β activity has been shown to negatively impact BMP activity ( 46 , 47 ). To address this possibility, gnptab –/– morphants were treated at 52 hpf with the TGFBRI inhibitor SB505124 (10 μM).…”
Section: Resultsmentioning
confidence: 99%
“…SKIL encodes the Ski-related novel protein N (SnoN) which is associated with the TGF β /SMAD pathway and, as the studies show, also with the pathway dependent on the p53 gene, which plays a key role in carcinogenesis [ 52 , 53 ]. Cao et al showed a strong correlation between the expression of SKIL and TGF β 1 of hepatocellular carcinoma; the level of expression of which was significantly elevated compared to controls [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, BMPs binding to BMPRI/I can block the activation of TGFβ receptors via upregulating CTGF itself and SMAD6. Moreover, one pathway can overcome the other when competing for the use of SMAD4 [148]. The type I membrane glycoprotein endoglin was found to act as a modulator of the relative impact of the TGFβ and BMP axes on malignancy in Ewing sarcoma and melanoma cells.…”
Section: Crosstalk Between Bmp and Tgfβ Pathway In Cancermentioning
confidence: 99%